Clinical handbook of psychological disorders a step-by-step treatment manual - Barlow, David H. (Guilford Press, 2008)
Offers students and practitioners with guidelines for treating frequently encountered adult disorders. This book presents background knowledge on each problem, describes the conceptual and empirical bases of their respective approaches, and details the nuts and bolts of evidence-based assessment and intervention, including clinical illustrations.